The Impact of Incorporating Phosphor Into Liquid Organic Fertilizer Media on The Production of Pigment and Protein in Spirulina sp. - Kintoko, Wendy Almira; Wijihastuti, Risa Swandari; Noriko, Nita (EXSACT-A, 2023)
Spirulina sp., a type of blue-green microalgae, possesses various beneficial properties such as antioxidants, probiotics, proteins, pigments, and carbohydrates, enabling it to generate a wide range of useful products. Previous studies using commercial fertilizers as the growth medium, have not achieved optimal pigment and protein production. Therefore, this study aims to investigate the impact of combining liquid organic fertilizer derived from Canna indica waste with TSP (Triple Super Phosphate) fertilizer on changes in pigment and protein production in Spirulina sp. The study was conducted for 16 days using a completely randomized design, with four replicates for each of the six treatments, along with a control. The results demonstrated a prolonged logarithmic growth phase, with the highest dry biomass weight observed on the 16th day in the treatment 1A (1,585 gr/L). Treatment 1A exhibited the highest levels of allophycocyanin and phycoerythrin pigments (9,861 mg/L and 4,319 mg/L, respectively), while treatment 1C yielded the highest protein content (0.33%). Statistical analysis on day 12, with a 95% confidence level, revealed significant differences in pigment production between various treatment groups. The study suggests that a phosphor concentration of 20 ppm is optimal for cultivating Spirulina sp.